PENINGKATAN HASIL BELAJAR SISWA KELAS XI SMK MENGGUNAKAN PENDEKATAN PROBLEM BASED LEARNING PADA MATERI LOGIKA MATEMATIKA - Sulistia Widayanti; Rippi Maya; Gida Kadarisma (IKIP Siliwangi, 2022)
During the covid-19 pandemic, learning in schools became limited. However, as time goes by, face to face learning had to continue in order to achieve maximum learning outcomes. The purpose of this study was to determine the improvement of student learning outcomes in class XI in a Vocational High Schools in Cimahi City by using a Problem Based Learning approach to the material of mathematical logic. This research is a classroom action research method which was conducted on 12 students in the 2021/2022 academic year.The test instrument is a posttest consisting of 4 essay questions, which are given in cycle I and cycle II. The results of this study indicate that there is an increase in learning outcomes from cycle I to cycle II. The average value of the class in cycle I did not meet the KKM. In cycle II, the average value of the class has increased, so that it reaches the KKM.